Double Infection of Onion yellow dwarf virus and Shallot latent virus in Garlic from Several Regions in Indonesia - Nurenik Nurenik; Sedyo Hartono; Sri Sulandari; Susamto Somowiyarjo; Argawi Kandito (Jurnal Perlindungan Tanaman Indonesia, 2021)
Viruses have been a problem on garlic cultivations in various countries. There are several viruses reported infecting garlic. Genera Potyvirus and Carlavirus are the most common viruses found infecting garlic. Mixed infection on garlic is often designated as a “garlic viral complex”. These viruses can be transmitted through imported garlic seeds. Therefore, it is necessary to conduct early detection of garlic seeds to prevent the epidemic of these viruses. This study aimed to detect Onion yellow dwarf virus (OYDV) and Shallot latent virus (SLV) on garlic. Garlic samples were obtained from Enrekang, Magelang, Temanggung, Tawangmangu, and Yogyakarta. Total RNA was extracted from the samples and subsequently used for RT-PCR using two pairs of specific primers SLV-F/SLV-R and OYDV-F/OYDV-R. Primary pair SLV-F/SLV-R in amplicons sized 276 bp, while OYDV-F/OYDV-R in amplicons sized 112 bp. RT-PCR results showed that OYDV was found in all samples tested in this study. Meanwhile, double infections (OYDV and SLV) were found in eight out of ten samples tested. These results indicated that double infections on garlic were common in Indonesia.